1996
DOI: 10.1037/0735-7044.110.6.1271
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in cortical function after medial frontal lesions in rats.

Abstract: The effects of sex on the performance of 4 spatial mazes (Morris water task, landmark task, radial arm maze, and egocentric radial arm maze) were studied in male and female rats given medial frontal lesions. Operated rats from both sexes were impaired at all of the tasks, but the frontal males were much less impaired than frontal females on the Morris task and the radial arm maze, both of which require animals to use multiple visual-spatial cues for their successful solution. Males also performed better on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
31
2
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 36 publications
9
31
2
1
Order By: Relevance
“…We found that neuroblast production was more robust in the injured P6 than in P10 animals. These data are reminiscent of those generated in experiments performed by Bryan Kolb et al [28,29], who found that with aspiration lesions of the prefrontal cortex there was a dramatic regenerative response that was most robust in P10 animals. That we see a more robust response in slightly younger animals in the somatosensory cortex is consistent with the concept that there is a caudal-to-rostral gradient in neocortical maturation.…”
Section: Discussionsupporting
confidence: 56%
“…We found that neuroblast production was more robust in the injured P6 than in P10 animals. These data are reminiscent of those generated in experiments performed by Bryan Kolb et al [28,29], who found that with aspiration lesions of the prefrontal cortex there was a dramatic regenerative response that was most robust in P10 animals. That we see a more robust response in slightly younger animals in the somatosensory cortex is consistent with the concept that there is a caudal-to-rostral gradient in neocortical maturation.…”
Section: Discussionsupporting
confidence: 56%
“…The contrasting morphological effects in medial and lateral prefrontal cortices and sexually dimorphic differences suggest that the effect of stressful experiences on these areas will also be sex-dependent. This may partially explain the reasonably consistent increase in anxiety-like behavior that is caused by stress during development in males but not females and sex differences in the effects of prefrontal lesions both during early development and in adulthood [42, 43]. Our data indicate a reduction of spine density only in males, which may be linked to the MS procedure.…”
Section: Discussionmentioning
confidence: 43%
“…Similar to humans, sex-related visuospatial performance differences have been described using the Morris water maze [Isgor and Sengelaub, 1998;Roof and Havens, 1992]. Lesion studies demonstrated that frontal lesions induced significantly greater disruption of spatial performance in female than in male rats [Kolb and Cioe, 1996] whereas lesions of the entorhinal cortex affected male more than female rats [Roof et al, 1993]. Thus, it appears promising to investigate human sex-related differences in visuospatial cognition by targeting these dimorphisms in functional neuroanatomy.…”
Section: Introductionmentioning
confidence: 93%